Effects of Carrageenan and Isolated Soy Protein Addition on the Physicochemical and Sensory Properties of Chicken Sausages - Afidah, Ulil; Aziz, Fariz Nurmita; Hasniah, Nurul (Journal of Applied Food Technology, 2025)
The global demand for healthier meat products has increased due to consumer concerns over synthetic additives and interest in functional ingredients. This study investigated the effects of carrageenan and isolated soy protein (ISP) on the physicochemical and sensory properties of chicken sausages. Sausages were formulated with either 2% or 4% carrageenan or ISP and evaluated for moisture content, water activity (aw), water holding capacity (WHC), pH, color (L*, a*, b*), and sensory attributes (taste, aroma, texture, overall acceptability). Results indicated no significant differences in moisture content, aw, WHC, or color among treatments. However, the addition of 4% carrageenan significantly increased the pH. Sensory evaluation showed that while carrageenan treatments maintained favorable sensory scores, a high concentration of ISP (4%) resulted in a significantly lower texture and acceptability score. These findings suggest that carrageenan is a more suitable natural additive than ISP for improving certain quality characteristics of chicken sausages without compromising consumer preferences.